2001
DOI: 10.1523/jneurosci.21-24-j0003.2001
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptors Drive the Endocannabinoid System in Hippocampus

Abstract: Endocannabinoids are key intercellular signaling molecules in the brain, but the physiological regulation of the endocannabinoid system is not understood. We used the retrograde signal process called depolarization-induced suppression of inhibition (DSI) to study the regulation of this system. DSI is produced when an endocannabinoid released from pyramidal cells suppresses IPSCs by activating CB1R cannabinoid receptors located on inhibitory interneurons. We now report that activation of group I metabotropic gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
304
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(325 citation statements)
references
References 44 publications
17
304
0
4
Order By: Relevance
“…Interestingly, we found that suspending synaptic activation or pharmacological blockade of mGluR also led to the extension of the cortical-tothalamic cooperation window, suggesting that synaptic activation, presumably through activation of mGluR leads to the release of eCBs that acting on CB1 receptors restricts synaptic cooperation. This is supported by previous studies showing a modulation of eCBs release by mGluR activation (Varma et al, 2001;Azad et al, 2004). Our results do not suggest that CB1 receptor activation regulates the synthesis of PRPs but rather modulates the ability of thalamic synapse to capture PRPs or to express LTP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, we found that suspending synaptic activation or pharmacological blockade of mGluR also led to the extension of the cortical-tothalamic cooperation window, suggesting that synaptic activation, presumably through activation of mGluR leads to the release of eCBs that acting on CB1 receptors restricts synaptic cooperation. This is supported by previous studies showing a modulation of eCBs release by mGluR activation (Varma et al, 2001;Azad et al, 2004). Our results do not suggest that CB1 receptor activation regulates the synthesis of PRPs but rather modulates the ability of thalamic synapse to capture PRPs or to express LTP.…”
Section: Discussionsupporting
confidence: 90%
“…We found that inhibition of CB1 receptors extends the time window for cortical-to-thalamic cooperation (Figure 5b), similar to what we observed when synaptic activation was suspended. eCBs can be released in the amygdala through the activation of metabotropic mGluRs (Azad et al, 2004;Varma et al, 2001); hence, one possibility is that synaptic activation triggers eCB release through mGluR activation. To test this, we repeated the experiment described above and inhibited mGluR activation by applying (RS)-a-MCPG (200 mM) during the time interval between weak thalamic stimulation and cortical strong stimulation (30 min).…”
Section: Synaptic Cooperation Between Cortical and Thalamic Inputs Hamentioning
confidence: 99%
“…Indeed, Varma et al (2001) (and later Ohno-Shosaku et al, 2002a) confirmed that group I mGluR activation also led to the production of endocannabinoids in hippocampal CA1 cells, and showed that this pathway, although not mediating DSI, had a powerful modulatory effect on the phenomenon. Further work extended these findings by showing that the activation of muscarinic receptors of the m1 and m3 subtypes had effects similar to those of group I mGluR activation (Martin & Alger, 1999;Kim et al, 2002;Ohno-Shosaku et al, 2003).…”
Section: The G-protein Coupled Receptor Pathway Of Retrograde Inhibitionmentioning
confidence: 87%
“…It has been demonstrated in a number of brain regions that activation of group I mGluRs inhibits GABAergic synaptic transmission indirectly via the endocannabinoid system (Maejima et al, 2001;Varma et al, 2001;Ohno-Shosaku et al, 2002;Galante and Diana, 2004). We therefore examined whether the TBOAinduced inhibition of GABAergic transmission was also mediated via endocannabinoids within the PAG.…”
Section: Tboa and Group I Mglur Activation Reduce Gabaergic Transmissmentioning
confidence: 99%